AN ANALYSIS OF LINGUISTIC STUDIES ON MAJOR FICTION BY JANE AUSTEN - Djuraeva, Madina (Журнал иностранных языков и лингвистики, 2023)
The current article is devoted to the critical analysis of linguistic studies on Jane Austen’s fiction. As one of the greatest novelists in English language and even regarded as being equal to the greatest dramatist William Shakespeare Jane Austin’s universal popularity lies in her ability to create the illusion of psychologically believable and self-reflecting characters. She is good at the penetrating revelation of characters, complex insight and sophisticated comic vision. In her novels, she searches for the harmony of personal desire and social norm, the growth of female selfhood and the interaction of present and memory, negotiation and relationship between different characters, which are closely related to her excellent mastery of language. However, Austen’s focus on three or four families in a country village as her writing subject misleads others to underestimate her art, and the critics just emphasize the wit, elegance and precision of her style without recognizing the originality and innovativeness of her language. Her superficially narrowness docs not necessarily mean she does not care about her art at all. On the contrary, she has been highly conscious of the use of language by exercising her own way towards the realization and solution to her art. She often expresses her awareness of language explicitly or implicitly in her letters to her family and friends, and thus her insistence on faithful and neat writing is quite obvious and her style is consistent with growth and improvement. Speculations on her artistic development are quite meaningful and necessary to enlarge the horizon to understand Austen’s fiction.